Sensitivity of Multivariate Tests of the Capital Asset-Pricing Model to the Return Measurement Interval. - Handa, Puneet; Kothari, S P; Wasley, Charles (Journal of Finance, 1993)
The capital asset pricing model's (CAPM) primary empirical implication is a positively sloped linear relation between a security's expected rate of return and its relative risk (beta). Recent research indicates that inferences about the risk-return relation are sensitive to the choice of the return measurement interval. The authors perform multivariate tests of the Sharpe-Lintner CAPM using monthly and annual returns on market-value-ranked portfolios. The CAPM is rejected using monthly returns, a result consistent with previous research. In contrast, the authors fail to reject the CAPM when annual holding period returns are used.